2018
DOI: 10.48550/arxiv.1811.11343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Finding a Nonnegative Solution to an M-Tensor Equation

Abstract: We are concerned with the tensor equation with an M-tensor, which we call the M-tensor equation. We first derive a necessary and sufficient condition for an M-tensor equation to have nonnegative solutions. We then develop a monotone iterative method to find a nonnegative solution to an Mtensor equation. The method can be regarded as an approximation to Newton's method for solving the equation. At each iteration, we solve a system of linear equations. An advantage of the proposed method is that the coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…There are also a few methods that can solve M-Teq (1.1) without restriction b ∈ R n ++ or that A is an M tensor. Those methods include the splitting method by Li, Guan and Wang [18], and Li, Xie and Xu [15], the alternating projection method by Li, Dai and Gao [17], the alternating iterative methods by Liang, Zheng and Zhao [23] etc.. Related works can also be found in [4,5,16,24,29,30,31,32,33,34].…”
Section: Definition 11 [3]mentioning
confidence: 99%
See 2 more Smart Citations
“…There are also a few methods that can solve M-Teq (1.1) without restriction b ∈ R n ++ or that A is an M tensor. Those methods include the splitting method by Li, Guan and Wang [18], and Li, Xie and Xu [15], the alternating projection method by Li, Dai and Gao [17], the alternating iterative methods by Liang, Zheng and Zhao [23] etc.. Related works can also be found in [4,5,16,24,29,30,31,32,33,34].…”
Section: Definition 11 [3]mentioning
confidence: 99%
“…However, in many cases, the standard Newton method may fail to work or loss its quadratic convergence property when applied to solve tensor equation (1.1). We refer to [18] for details.…”
Section: Definition 11 [3]mentioning
confidence: 99%
See 1 more Smart Citation
“…As an application, a tensor splitting algorithm for solving the multi-linear model of higher-order Markov chains was proposed. Li et al, in [16] firstly derived a necessary and sufficient condition for an M-tensor equation to have nonnegative solutions. Secondly, developed a monotone iterative method to find a nonnegative solution to an Mtensor equation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the state-of-the-art solvers, e.g., HM and QCA, tailored for (1.3) with a positive vector b may not produce a desired nonnegative solution in some situations. In addition, just after this article has been completed, Li, Guan and Wang [12] proposed an algorithm for finding a nonnegative solution of the multilinear system (1.3). It is shown that an increasing sequence is generated by the algorithm in [12] and it converges to a nonnegative solution of the multilinear system (1.3), while our proposed algorithm produces a decreasing sequence.…”
Section: Introductionmentioning
confidence: 99%